Temporal Change in Silica Accumulation, Covariations with Foliar Minerals and Fodder Value of Loxodera Ledermannii (Pilger) Ex Launert from the Sudanian Benin (Western Africa) - Kindomihou, M. Valentin; HOLOU, R.A.Y.; Dagbénonbakin, D. Gustave; SINSIN, Brice; Meerts, Pierre (My University, 2012)
Silica in forage grasses has been found to be an important factor in reducing cell-wall constituents’ digestibility. As the more the silica concentration, the less the grasses digestibility, techniques for silica reduction in grasses are needed. The silica rate reduction might induce other important nutrients ‘reduction. This study examines temporal change in Loxodera ledermannii (Pilger) chemical composition and silica concentration in leaves from individuals collected at 15-days intervals from April to October in W National Park. Some 100 g of fresh leaves from 90 clumps were oven dried and analyzed for silica, Ashes, N, Na, Ca, P, K, Mg. Digestible Nitrogen Matter and Fodder Energetic value were calculated using Demarquilly formula. SiO2 negatively related to K, P, N and UF, but positively to MAD, Ashes and Ca. This suggests that SiO2 concentration could be reduced without affecting significantly the concentration of the important nutrients such as Ashes and MAD.
Keywords: Loxodera ledermannii; silicification; chemical traits; fodder value; sudanian Benin